PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), SIZE, DAN INTEREST BASED DEBT (IBD) TERHADAP NILAI PERUSAHAAN KOMPONEN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Fatmawati Sholichah; Rusli, Aditya; M. Nasikh (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2026)
Finance is a crucial component of a company. Therefore, a company aims to maximize profits to enhance the prosperity of its shareholders and owners. Therefore, sound financial management will help achieve this goal. Furthermore, a company's goal is to maximize its value. Factors influencing company value include Corporate Social Responsibility (CSR), size, and interest-based debt. Therefore, the purpose of this study is to determine and analyze the effect of corporate social responsibility on the value of Automotive Component companies listed on the Indonesia Stock Exchange for the 2020-2024 period, to determine and analyze the effect of size on the value of Automotive Component companies listed on the Indonesia Stock Exchange for the 2020-2024 period, to determine and analyze the effect of interest-based debt on the value of Automotive Component companies listed on the Indonesia Stock Exchange for the 2020-2024 period, and to determine and analyze the effect of corporate social responsibility, size and interest-based debt on the value of Automotive Component companies listed on the Indonesia Stock Exchange for the 2020-2024 period. This research uses a quantitative research approach. The analytical method used in this study is a quantitative data analysis method using multiple linear regression. Based on the first research hypothesis test, it shows that the Corporate Social Responsibility variable (X1) has a significant and positive influence on the Company Value variable (Y). Then the Size variable (X2) has a negative and significant influence on the Company Value variable (Y). The Interest Based Debt variable (X3) has a significant and positive influence on the Company Value variable (Y). Finally, the Corporate Social Responsibility, Size, and Interest Based Debt variables have a significant and positive influence on the Company Value variable (Y). Keywords : Corporate Social Responsibility, Size, Interest Based Debt